Anthrax : the investigation of a deadly outbreak - Guillemin, Jeanne, 1943- (University of California Press, 1999)
This is a powerful story of an anthrax outbreak 20 years ago, one that took the lives of over 150 Russians, and one that was covered up by the KGB and others in the government. Like a mystery novel, the book's drama takes the reader through the maze of cover-up and denial to find the real truth.